ALUMINOUS WEBSTERITE AND GRANULITE XENOLITHS FROM THE CHYULU HILLS VOLCANIC FIELD, KENYA: GABBRO-TROCTOLITIC CUMULATES SUBJECTED TO LITHOSPHERIC FOUNDERING - Ulianov A.; Kalt A.; Pettke T. (My University, 2006)
Whole rock major and trace element abundances in aluminous garnet-spinel websterite, sapphirine-bearing Mg-Al granulite and hibonite-bearing Ca-Al granulite xenoliths from the Chyulu Hills volcanic field, Kenya, suggest that the samples represent a meta-igneous suite linked by fractionation. The incompatible major element contents increase from the websterites to the Mg-Al granulites and further to the Ca-Al granulites. High bulk rock Mg#s and very low concentrations of most incompatible trace elements indicate that the rocks are cumulates rather than crystallized melts. Elevated Ni abundances, impoverishment in Cr and HFSE and high contents of normative plagioclase and olivine in the granulites indicate that their protoliths were similar to troctolite. The textures and metamorphic reaction paths recorded in the granulites suggest igneous emplacement in the crust and cooling from igneous to ambient crustal temperatures accompanied or followed by compression. For the websterite xenoliths, there is an apparent contradiction between the results of P-T calculations that suggest high P and T of crystallization of early generation pyroxenes and elevated P-T conditions during final equilibration (1.4-2.2 GPa/740-980°C) on the one hand and the positive Eu anomaly that suggests shallow-level plagioclase accumulation on the other hand. This contradiction can be reconciled by a model of compression of a plagioclase-bearing (gabbroic) protolith to mantle depths where it recrystallized to an ultramafic assemblage, which requires foundering of dense lower crustal material into the mantle. © Springer-Verlag 2006.